Evolution of rock brittleness under mechanical and thermal effects - Wang, Lu (Nanyang Technological University, 2023)
Understanding rock brittleness plays an essential role in controlling the drilling and cutting efficiency in rock engineering for construction and energy applications. Numerous brittleness indices have been proposed to quantify rock brittleness under static and dynamic loads. However, rock brittleness under complex mechanical and thermal conditions has yet to be explicitly evaluated. In this thesis, a series of split Hopkinson pressure bar (SHPB) and Cerchar abrasivity index (CAI) tests are conducted experimentally and numerically to reveal the evolution of rock brittleness on rock materials under different mechanical and thermal conditions.